PENERAPAN ALGORITMA TRANSPORTASI UNTUK OPTIMALISASI DISTRIBUSI BIBIT PADI - Obo Raba, Gusti Devretes; Selviana Adoe, Vera; Tapatab, Alfin Yahya; Ezra Yane Taemnanu (LPPM Universitas Bina Bangsa, 2024)
The application of transportation algorithms in distributing rice seedlings at PT Sriwijaya aims to optimize operational costs and logistics efficiency. This study analyzes the distribution process of rice seedlings from warehouses in Noelbaki and Kolbano to various agents using the software POM-QM for Windows. The transportation method was chosen to determine the most efficient allocation and shipping routes, focusing on reducing distribution costs. Data collected through observations and interviews indicate that the company faces challenges in-stock availability and high distribution costs. The analysis results show that transportation algorithms can reduce distribution costs by up to 25% while ensuring that all agent demands are optimally met. This study emphasizes the importance of applying mathematical methods in distribution management to enhance PT Sriwijaya's competitiveness in the agricultural sector.